Instrumentos e atividades realizadas para a coleta de um corpus de aprendizes em língua inglesa para integrar o Br-ICLE (The Brazilian Portuguese Sub-corpus of ICLE) - Paiva, Paula Tavares Pinto [UNESP] (My University, 2013)
This paper presents and discusses initiatives taken in a public university in the state of São Paulo in order to collect and organize a corpus composed of argumentative texts to be part of Br-ICLE – a subcorpus of ICLE1 – which is composed of texts produced by Brazilian students enrolled in the courses of Arts and Languages and Translation. The discussion is based on a three-year project in which we could observe underuse and overuse features in the texts produced by Brazilian undergraduate students.

O objetivo deste trabalho é apresentar e discutir as iniciativas tomadas em uma universidade pública do estado de São Paulo com o intuito de coletar e organizar um corpus de textos argumentativos que ajudará a compor o Br-ICLE – o subcorpus do ICLE, composto por textos em língua inglesa produzidos por alunos brasileiros dos cursos de Licenciatura em Letras e Bacharelado em Letras com Habilitação em Tradução. A discussão tomará como base o desenvolvimento do projeto durante três anos de ocorrência, no qual puderam-se observar características de subuso e sobreuso nos textos dos alunos brasileiros.
Tools and activities used in data collection for a corpus composed of texts written by students of English language to be added to Br-ICLE (Brazilian Portuguese Sub-Corpus of ICLE
Keywords: Linguística de corpus; corpora de aprendizes; Características de subuso e sobreuso da língua inglesa; corpus linguistics; learner corpus; underuse and overuse features of English